Fundamentals of electrical machines study aid - Tyuteva, P. V. specialist in the field of electrical engineering associate Professor of Tomsk Polytechnic University, candidate of technical Sciences 1983- (Tomsk Polytechnic University Publishing House, 2022)
The study aid provides a description of the main structures, the basic theory, as well as the operational characteristics of electrical machines and transformers. The manual gives questions for self-examination. The textbook can be useful in studying the discipline "Professional foreign language" for students 13.03.02 Power and electrical engineering, as well as in the study "Electrical machines" for students under academic exchange programs in English